GRACE Combined with WSD to Assess the Change in Drought Severity in Arid Asia - Jiawei Liu; Guofeng Zhu; Kailiang Zhao; Yinying Jiao; Yuwei Liu; Mingyue Yang; Wenhao Zhang; Dongdong Qiu; Xinrui Lin; Linlin Ye (Remote Sensing, 2022)
Gravity Recovery and Climate Experiment (GRACE) satellite data are widely used in drought studies. In this study, we quantified drought severity based on land terrestrial water storage (TWS) changes in GRACE data. We used the water storage deficit (WSD) and water storage deficit index (WSDI) to identify the drought events and evaluate the drought severity. The WSDI calculated by GRACE provides an effective assessment method when assessing the extent of drought over large areas under a lack of site data. The results show a total of 22 drought events in the central Asian dry zone during the study period. During spring and autumn, the droughts among these incidents occurred more frequently and severely. The longest and most severe drought occurred near the Caspian Sea. In the arid area of central Asia, the north of the region tended to be moist (the WSDI value was 0.04 year−1), and the south, east, and Caspian Sea area tended to be drier (the WSDI values were −0.07 year−1 in the south, −0.11 year−1 in the east, and −0.19 year−1 in the Caspian Sea). These study results can provide a key scientific basis for agricultural development, food security, and climate change response in the Asian arid zone.